Exploring the Relationship Between Neighborhood-Built Environment and Elderly Health: A Research Based on Heterogeneity of Age and Gender Groups in Beijing - Li, Jingwei; Tian, Li; Ouyang, Wei (Frontiers in Public Health, 2022)
Background: The built environment quality of neighborhoods has significant impacts on the elderly health. Although there has been a wealth of studies in low-density Western cities, research of the impacts of built environment on elderly health in high-density Chinese cities is far from sufficient. The pathways by which the built environment affects elderly health remain to be observed, particularly whether such pathways vary for different ages and genders. Methods: Based on the data of the “Fourth Survey on the Living Conditions of the Elderly in China” in 2015, a sample survey of 3360 older adults in Beijing was conducted. We first explored the built environment factors that affect elderly health with a multilevel regression model. We then adopted a multilevel structural equation model to reveal the mediating effect of health activities. Moreover, a stratified analysis was applied to explore the impact of age and gender heterogeneity on the relationship between built environment and elderly health. Results: (1) Neighborhood built environment measured within a 500m buffer area had a higher correlation with elderly health when compared with other areas. (2) Physical activity and social interaction played a mediating role in the correlation between built environment and elderly health. Even if the interference of residential self-selection was controlled within the subgroups, most of the built environment elements had significant impacts on elderly health. (3) The impacts of built environment variables on elderly health vary among different age and gender groups. Population density mainly promoted health through health activities in the middle-aged (aged 70-79) group and high-aged (aged 80+) group, shorter distance to transit stations affects health by promoting social interaction for high-aged males (aged 80+) group compared with other groups, and high-quality built environment significantly promotes physical activity to alleviate loneliness only in elderly females. Conclusion: To effectively boost elderly health by improving the quality of built environment, adequate considerations should also be given to the differentiated demands of adults of different age and gender groups, precise health behavior interventions should be provided, and the construction of personalized aging-friendly and livable spatial environments should be emphasized to realize healthy and active aging.